Prostitution in Colombia: a phenomenon anchored to power and new forms of contractual exploitation - Forero Montoya, Jorge Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Through the methodology of critical discourse analysis, this article examines current prostitution as a phenomenon anchored in various power matrices, which trace a network of domination and colonization of the body that is somewhat legitimized by neoliberal dynamics and from what Carole Pateman (1995) understands as a sexual contract. The Colombian case and the current legal evolution of the phenomenon of prostitution are presented, and it is found that in the country there is a tendency towards the regulation of the same, under a discourse on the labor rights of sex workers, however unaware that the recognition of said rights do not necessarily counteract the phenomena of precarious economy mapping and lack of real opportunities. This means that in contexts of domination and unequal hierarchy, women are exploited and the existence of human trafficking is facilitated.